(untitled) - Gautier, Catherine (New York, 2008)
The vast majority of climate scientists now agree that human-induced climate change is a reality, but there is much ongoing research and debate. Nevertheless, our global society is confronted with the urgent need for a wise response to potential climate change. This volume brings together scientists from the US and Europe to review the state-of-the-art in climate change science. It draws from the most recent assessment reports of the IPCC, but scientific jargon has been minimized for readers from different backgrounds. Each chapter provides a description of a particular aspect of the climate problem, its role in current climate change, its potential future impacts, and its societal importance. This book is written for scientists and students in a wide range of fields, such as atmospheric science, physics, chemistry, biology, geography, geology and socioeconomics, who are seeking a coherent and broad review of climate change issues
Keywords: Hydrologic cycle,Global temperature changes,Atmospheric chemistry,Không khí hóa học; Environmental aspects,Khía cạnh môi trường